Negara Ideal Perspektif Nurcholish Madjid: Telaah Asas Keislaman, Keindonesiaan, dan Kemodernan serta Relevansinya Terhadap Pendidikan Kewarnegaraan dan Model Tata Negara Indonesia - Arsyad, Fahmi (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2026)
This study examines the relationship between Islam, Indonesian identity, and modernity in NurcholishMadjid’s conception of the state and its relevance to Indonesia’s constitutional system. The issue of relationsbetween religion and the state within the context of the nation-state constitutes the main background of thisresearch, particularly in a plural society such as Indonesia, which adopts Pancasila as its state ideology.Nurcholish Madjid’s thought is selected because it offers a substantive approach that rejects theformalization of Islam as a state ideology while emphasizing the internalization of Islamic ethical values innational and state life. This research employs a qualitative approach with a library-based research designthrough the analysis of Nurcholish Madjid’s works and other relevant scholarly sources. The findingsindicate that Nurcholish Madjid’s concept of the state positions the state as a worldly institution that mustbe governed rationally, democratically, and justly. The integration of Islamic values as a moral orientation,Indonesian identity as a national context, and modernity as a framework of rationality produces an inclusiveand adaptive conception of the state. The relevance of this thought is reflected in various aspects ofIndonesia’s constitutional order, including the rule of law, democracy, social justice, good governance, andthe affirmation of pluralism. This study concludes that Nurcholish Madjid’s thought makes a significantcontribution to the development of constitutional law discourse in Indonesia by offering a synthesis ofreligious values, nationalism, and modernity as the foundation for building a democratic, pluralistic, andcivilized state.Keywords: Country, Relevance, Nurcholish Madjid